Curing characteristics of low molecular weight melamine-urea–formaldehyde (MUF) resin-impregnated poplar wood. (28th March 2022) - Li, Zhonghao; Zhang, Xiaomeng; Song, Shasha; Xu, Kang; Lyu, Jianxiong; Li, Xianjun
Highlights: The curing characteristics of low molecular weight melamine-urea–formaldehyde (LMW-MUF) resin-impregnated wood (RIW) were studied. With the increase in LMW-MUF resin solution concentration, the resin curing reaction in RIW was more difficult. Due to the wood steric hindrance, the resin curing reaction in RIW was slower than the LMW-MUF resin solution itself. The time–temperature-curing degree function of LMW-MUF resin solution in RIW was fitted during the curing process. Abstract: The curing characteristics of low molecular weight melamine-urea–formaldehyde (MUF) resin within impregnated wood during the drying process remain unclear, making the setting and optimization of the drying process highly challenging. As a result, drying efficiency and drying quality of resin-impregnated wood (RIW) are limited. This study explores the effects of resin solution concentration (moisture content) and wood on resin curing characteristics to facilitate the development and optimization of the drying schedule for RIW. Poplar wood ( Populus tomentosa ) impregnated with 20%, 30%, 40%, and 50% MUF resin solutions were analyzed by differential scanning calorimetry (DSC). The optimum curing temperature was obtained by extrapolation. Kinetic parameters of curing reaction of resin-impregnated wood were calculated using the Kissinger differential method, Ozawa integral method, and Crane equation. Subsequently, the function of curing time–temperature-curing degree of MUF RIW was obtained. The peak temperature shifts to a higher temperature with increased RIW moisture. The optimum curing temperatures of the four RIW samples were 103.50, 98.05, 91.34, and 84.28 °C, respectively, while their corresponding apparent curing reaction activation energies were 117.58, 91.92, 81.34, and 63.38 kJ/mol, respectively. The relationship between curing degree and curing time under 50, 60, 70, and 80 °C isothermal conditions was simulated based on the kinetic parameters of resin curing. Additionally, the complete curing time of RIW with different moisture contents was estimated under different isothermal conditions. Parametric analysis and calculation based on the kinetic model of curing reaction showed that the moisture and wood hinder the curing and cross-linking of the resin, and the curing time increases with moisture content. This study could provide data support for the drying of RIW.